Effects of Liquidity on Profitability of Commercial Banks in Nepal - Sigdel, Kamal; Deswal, Kirti (Nepalese Journal of Business, 2025)
Bank liquidity refers to the ability of the bank to ensure the availability of funds to meet financial commitments or maturing obligations at a reasonable price at all times. The liquidity of the banking sector has historically faced challenges stemming from a variety of factors. Nepal’s financial system is characterized by a dominance of commercial banks, limited diversification of financial instruments, and a relatively low level of f inancial inclusion. This study examines the effect of liquidity on the performance of Nepalese commercial banks. The descriptive, correlational & multiple regression model has been used for analysis of the data. The sample banks are selected using the purposive sampling approach with 50 observations for the period of 2012/13 to 2021/22. Out of the total population, five leading private commercial banks were selected based on their paid-up capital which comprised 25.00 percent of the total population of commercial banks in Nepal. The pooled data of five commercial banks (Nabil Bank Limited, Himalayan Bank Limited, Everest Bank Limited, Nepal Investment Mega Bank Limited and Nepal SBI Bank Limited) out of total population of twenty commercial banks up to November 2024 has been analyzed. For this study, the descriptive and causal comparative research designs have been used. The study uses independent variables such as Liquid Fund to Current Liabilities Ratio (LFTCLR), Total Liquid Fund to Total Deposit Ratio (LFTDR), Total Liquid Fund to Total Deposit Ratio (LFTDR), Cash in hand to Total Deposit Ratio (CHTDR) & Cash and Bank Balance to Total Deposit Ratio (CABTDR) and dependent variables (return on equity and return on assets). The results showed that specific financial indicators, such (Liquid Fund to Current Liabilities Ratio (LFTCLR), Total Liquid Fund to Total Deposit Ratio (LFTDR), Total Liquid Fund to Total Deposit Ratio (LFTDR), Cash in hand to Total Deposit Ratio (CHTDR) & Cash and Bank Balance to Total Deposit Ratio (CABTDR); play crucial roles in influencing ROA and ROE. Major issue on liquidity are highlighted. Identified that, liquidity significantly impact bank profitability, as evidenced by their bivariate correlation with returns on assets (ROA) and returns on equity (ROE). The analysis revealed that the Liquid Fund to Total Deposit Ratio (LFTDR),NRB Balance to Total Deposit Ratio (NRBTDR), and Cash in hand to Total Deposit Ratio (CHTDR) significantly contribute to predicting ROA. A positive association was observed for LFTDR, indicating that an increase in the ratio of liquid funds to total deposits corresponds to a higher predicted ROA. Similarly, NRBTDR demonstrated a positive impact, signifying that a greater reliance on non-resident balances relative to total deposits is associated with an elevated predicted ROA. In contrast, CHTDR displayed a negative relationship, suggesting that an increase in the ratio of cash in hand to total deposits is linked to a decrease in the predicted ROA. Conversely, the ratios of Liquid Fund to Current Liabilities (LFTCLR) and Cash and Bank Balance to Total Deposit (CABTDR) did not exhibit statistically significant relationships with ROA, implying their limited role in explaining variability in the financial performance of the sample banks. Moreover, the analysis highlights the interconnectedness of various financial metrics with bank profitability.